1999
DOI: 10.1021/ic990429v
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Lanthanide Coordination Polymers

Abstract: One-dimensional lanthanide coordination polymers with the formula Ln(isonicotinate)3(H2O)2 (Ln = Ce, Pr, Nd, Sm, Eu, Tb; 1a−f) were synthesized by treating nitrate or perchlorate salts of Ln(III) with 4-pyridinecarboxaldehyde under hydro(solvo)thermal conditions. Single-crystal and powder X-ray diffraction studies indicate that these lanthanide coordination polymers adopt two different structures. While Ce(III), Pr(III), and Nd(III) complexes adopt a chain structure with alternating Ln−(carboxylate)2−Ln and Ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(104 citation statements)
references
References 19 publications
3
100
0
1
Order By: Relevance
“…Herein, we report the synthesis and crystal structure of a new lanthanum complex with isonicotinic ligand. (Mao et al, 1998) and [La(C 6 H 4 NO 2 ) 2 (H 2 O) 4 ](NO 3 ) (Cai et al, 2003), but differs from those found in Ln(isonicotinate) 3 (H 2 O) 2 (Ln = Ce, Pr, Nd, Sm, Eu, Tb) (Ma, Evans et al, 1999), in which the Ln III atoms are bridged by four syn-syn µ-O:O′-carboxylate groups of the isonicotinic ligands (Ln = Ce, Pr, Nd) or coordinated by both two syn-syn µ-O:O′-carboxylate groups and chelating carboxylate groups of the isonicotinic ligands (Ln = Sm, Eu, Tb). To the best of our knowledge, the arrangement in the present complex is rare in the lanthanide analogs.…”
Section: S1 Commentmentioning
confidence: 93%
See 2 more Smart Citations
“…Herein, we report the synthesis and crystal structure of a new lanthanum complex with isonicotinic ligand. (Mao et al, 1998) and [La(C 6 H 4 NO 2 ) 2 (H 2 O) 4 ](NO 3 ) (Cai et al, 2003), but differs from those found in Ln(isonicotinate) 3 (H 2 O) 2 (Ln = Ce, Pr, Nd, Sm, Eu, Tb) (Ma, Evans et al, 1999), in which the Ln III atoms are bridged by four syn-syn µ-O:O′-carboxylate groups of the isonicotinic ligands (Ln = Ce, Pr, Nd) or coordinated by both two syn-syn µ-O:O′-carboxylate groups and chelating carboxylate groups of the isonicotinic ligands (Ln = Sm, Eu, Tb). To the best of our knowledge, the arrangement in the present complex is rare in the lanthanide analogs.…”
Section: S1 Commentmentioning
confidence: 93%
“…For lanthanide complexes with nicotinic acid, isonicotinic acid and isonicotinic acid N-oxide ligands, see : Cai et al (2003); Chen & Fukuzumi (2009) ;Cui et al (1999); Kay et al (1972); Ma et al (1996Ma et al ( , 1999; Mao et al (1998); Starynowicz (1991Starynowicz ( , 1993; Wu et al (2008); Zeng et al (2000); Zhang et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[7Ϫ9] Such systems are often tunable by making subtle changes to the reaction conditions, such as the choice of counterion and solution pH, that allow the deliberate design of compounds with luminescent, [10] superconducting [11,12] or magnetic properties [13,14] and also compounds that can be used as nanofibres, [15] in catalysis, [16] in separation processes, [17,18] for gas and liquid storage [19] and in nonlinear optics. [20,21] We have prepared previously one-dimensional coordination polymers of Ni II with aminobenzonitrile isomers and thiocyanate ions as ligands.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much current interesting on the coordination polymers consisting of lanthanide and multifunctional organic ligands for their novel structures and unique properties especially in magnetism, luminescence and catalysis [1][2][3]. Many studies were focus on the construction of higher-dimensional networks by employing the rigid multicarboxylate ligands as building blocks.…”
mentioning
confidence: 99%